COORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI WUJUD PELAYANAN PUBLIK NON BISNIS BERBASIS TANGGUNG JAWAB SOSIAL - S. Noorsyamsa Djumara (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
CSR as a company policy, continues to change over time. CSR as a sustainable commitment from businesses to behave ethically and contribute to economic development while improving the quality of employees and their family life aswell as the communities around the company. CSR has a social purpose –not economic. Obviously, consequence is in the context of ethics. CSR is an investment program for growth and sustainability and the company is no longer seen as a means of cost (cost centers) but rather as a means of making a profit (profit center). CSR program is the company's commitment to support the creation of sustainable development. The field data and the results of interviews and questionnaires given to the state-owned companies in the city of Bandung and Cimahi show that CSR program has aligned with the company's program. The companies are PT PLN, PT. Bio Farma, PT. Indonesia Railway Persero (KAI), PT Pegadaian Cabang Cimahi, PT PINDAD. However, there is no linkage program in coordination with the Regional Development Planning Board (BAPPEDA) at the regency and provincial level so that there is still need to programmatically harmonize performance in realizing the region welfare.